Induksi Kalus secara In Vitro dari Daun Cengkeh (Syizigium aromaticum L.) dalam Media dengan Berbagai Konsentrasi Auksin - Rasud, Yulianti; Bustaman, Bustaman (Jurnal Ilmu Pertanian Indonesia, 2020)
Clove is an important commodity in Indonesia and it is used as a main material for cigarettes. Clove propagation can be conducted by generative method, but this method takes a long time to produce a considerable number of seedlings. To overcome such problem, it can be applied a tissue culture technique. An effort has been conducted to induce calli from sliced clove leaves and performed at Plant Biotechnology Laboratory, Faculty of Agriculture, Tadulako University from June-November 2016. The aim of this experiment was to determine the most suitable type and concentration of auxins for callus induction of sliced clove leaves via in vitro culture. This experiment used a Completely Randomized Design with six treatments, namely 0.25 ppm 2.4-D; 0.50 ppm 2.4-D; 0.75 ppm 2.4-D; 0.25 ppm NAA; 0.50 ppm NAA; and 0.75 ppm NAA. Parameters observed consisted of the speed or time of appearance, the percentage, color, and texture of calli. Data were analyzed by using analysis of variance and differences between mean treatments were determined by Duncan Multiple Range Test at 5% level. The results of this experiment indicated that the type and concentration of auxin most suitable for callus induction of sliced clove leaves was culture medium supplemented with 0.75 ppm 2.4-D. In such medium composition, it was obtained the quickest callus formation, namely average 4.22 WAC with the percentage of callus formation was up to 100%. In general, the colors of calli were white, yellowish white, and brown; with the textures of formed calli were soft, compact, and intermediat. Keywords: callus formation, clove, growth hormone, tissue culture